Functional Human and Murine Tissue-Engineered Liver Is Generated from Adult Stem/Progenitor Cells. (30th August 2016) - Mavila, Nirmala; Trecartin, Andrew; Spurrier, Ryan; Xiao, Yi; Hou, Xiaogang; James, David; Fu, Xiaowei; Truong, Brian; Wang, Clara; Lipshutz, Gerald S.; Wang, Kasper S.; Grikscheit, Tracy C.
Abstract: Liver disease affects large numbers of patients, yet there are limited treatments available to replace absent or ineffective cellular function of this crucial organ. Donor scarcity and the necessity for immunosuppression limit one effective therapy, orthotopic liver transplantation. But in some conditions such as inborn errors of metabolism or transient states of liver insufficiency, patients may be salvaged by providing partial quantities of functional liver tissue. After transplanting multicellular liver organoid units composed of a heterogeneous cellular population that includes adult stem and progenitor cells, both mouse and human tissue-engineered liver (TELi) form in vivo. TELi contains normal liver components such as hepatocytes with albumin expression, CK19-expressing bile ducts and vascular structures with α-smooth muscle actin expression, desmin-expressing stellate cells, and CD31-expressing endothelial cells. At 4 weeks, TELi contains proliferating albumin-expressing cells and identification of β2-microglobulin-expressing cells demonstrates that the majority of human TELi is composed of transplanted human cells. Human albumin is detected in the host mouse serum, indicating in vivo secretory function. Liquid chromatography/mass spectrometric analysis of mouse serum after debrisoquine administration is followed by a significant increase in the level of the human metabolite, 4-OH-debrisoquine, which supports the metabolic and xenobiotic capability of human TELi in vivo. Implanted TELi grew in a mouse model of inducible liver failure.